Lower limb kinetic asymmetries in professional soccer players with and without anterior cruciate ligament reconstruction: nine months is not enough time to restore "functional" symmetry or return to performance - Read, P. J.; Auliffe, S. M.; Wilson, M. G.; Graham-Smith, P. (The American Journal of Sports Medicine, 2020)
Background: Residual between-limb deficits are a possible contributing factor to poor outcomes in athletic populations after anterior cruciate ligament reconstruction (ACLR). Comprehensive appraisals of movement strategies utilized by athletes at key clinical milestones during rehabilitation are warranted. Purpose: To examine kinetic parameters recorded during a countermovement jump with a force platform in healthy professional soccer players and to compare their performance with those who had undergone ACLR at different stages of their rehabilitation. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 370 male professional soccer players attended a physical screening assessment where they performed at counter jump movement protocol on dual force plates and were divided into 4 groups: group 1 (<6 months post-ACLR), group 2 (6-9 months post-ACLR), group 3 (>9 months post-ACLR), and group 4 (healthy matched controls). Results: Players in the later phases of rehabilitation increased their jump performance; however, values were significantly lower than those of healthy matched controls (P > .05). Significant between-limb differences were present for both eccentric- and concentric-phase variables (P < .05), with effect sizes ranging from moderate to very large (d = 0.42-1.35). Asymmetries were lower in players who were further away from surgery; however, between-limb differences remained significantly greater in players >9 months after ACLR versus matched controls—specifically, for concentric impulse, concentric peak force, eccentric deceleration impulse, and eccentric deceleration rate of force development asymmetry (P < .05). Logistic regression identified concentric impulse asymmetry as being most strongly associated with a history of ACLR when group prediction analysis was performed (ACLR group 1, 2, or 3 vs matched controls), with odds ratios ranging from 1.50 to 1.91. Conclusion: Between-limb deficits in key eccentric and concentric loading parameters remain >9 months after ACLR, indicating a compensatory offloading strategy to protect the involved limb during an athletic performance task. Concentric impulse asymmetry could be considered an important variable to monitor during rehabilitation.